Waterborne asbestos: Good practices for surface waters analyses - Avataneo, Chiara; Capella, Silvana; Luiso, Mariagrazia; Marangoni, Giuliana; Lasagna, Manuela; De Luca, Domenico A.; Bergamini, Massimo; Belluso, Elena; Turci, Francesco (Frontiers in Chemistry, 2023)
Asbestos occurrence has been mainly monitored in air so far and only limitedly considered in other matrices, such as water. Waterborne asbestos could originate from natural or anthropogenic sources, leading to non-conventional exposure scenarios. It could be a secondary source of airborne asbestos in case of water-to-air migration, particularly in case of surface moving water, such as in rivers and streams. The scarce attention dedicated to waterborne asbestos has led to a considerable fragmentation in regulatory approaches regarding the study of water samples possibly contaminated by mineral fibres. In this context, this study has been designed to test the reliability of an existing analytical method devoted to natural waters investigations. Following the operational protocol issued by the Piedmont (Italy) Environmental Protection Agency, Scanning Electron Microscopy analyses have been performed on a standard sample of waterborne chrysotile, mimicking stream water. The investigations have been performed by different operators and using different analytical setups, to verify whether the method applied has a good interlaboratory reproducibility and which could be the most error-prone analytical steps. Three data sets have been obtained on the same sample, showing a low reproducibility among each other. Possible reasons causing this discrepancy have been discussed in detail and good practices to perform reliable analyses on surface water samples containing asbestos have been proposed to help the regulatory organs to better define analytical protocols.